Die zeitliche Wirkung von Urteilen des EuGH Maßgaben des Unionsrechts und Reaktionsmöglichkeiten mitgliedstaatlicher Gerichte - Riegger, Stephan (Internationales Recht der Gegenwart, 2021)
Against the background of the interconnection between the Union legal order and the legal orders of the Member States, the temporal effect of ECJ judgments is one of the central elements of Union law. Following a careful analysis of the parameters of Union law that shape it, the book deals with the possibilities of courts of Member States to react to an interpretation of Union law by the ECJ whose effects have not been limited in time. By focusing in particular on the "enforcement dimension" of Union law, it contributes to determining the status of the primacy of Union law and makes the hybrid nature of interpretation in conformity with directives more visible.